Penerapan Data Mining Dengan Algoritma Apriori Untuk Analisa Pola Pembelian Pelanggan Pada Penjualan Martabak Surya Kencana - Albert, Bryan; Herwindiati, Dyah Erny; Sitorus, Manatap Dolok Lauro (Faculty of Information Technology, Universitas Tarumanagara, 2023)
The purpose of this study is to analyze customer buying patterns at Martabak Surya Kencana. The method used is the Apriori algorithm, the Apriori algorithm is one of the most well-known algorithms in data mining in finding data patterns or patterns of occurrence/data frequency. Usually the Apriori algorithm is used to find customer buying patterns at a minimarket based on purchase transactions. The results of this study are with a minimum support value of 20% and a minimum confidence value of 70%, it produces 2 rules, namely if you buy Martabak Telor 3 Super Eggs, you will buy Martabak Sultan Cheese with a support value of 26.8% and a confidence value of 79. 8% and if you buy